Effectiveness of Regional Property Management: A Study on Bandung City Department of Fire and Disaster Management - Ligar Hardika, Andhika; Ilyas, Supriyanto; Sugianto Yusuf, Paulus; Susiani, Rini (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effectiveness of regional management in the Department of Fire and Disaster Management in Bandung. The population in this study is the Secretariat in the fire and disaster management department. This study uses a trial with 30 respondents who are used to test research instruments taken from the population. Prerequisite test analysis includes a normality test, correlation test, model compatibility test, and hypothesis test. The research method used in this research is quantitative research with descriptive and verification research designs. This is also supported by the results of the determination coefficient of 75.90%, which shows that the government's internal control system influences the effectiveness of regional property management, and 24.10% is influenced by other factors not examined.